Preparation method of metal atom doped cobaltosic oxide water electrolysis catalyst
Patent Information
- Application Number
- CN202411316307.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-20
- Publication Date
- 2026-11-03
- Estimated Expiration
- 2044-09-20
AI Technical Summary
Existing oxygen evolution catalysts for water electrolysis prepared from precious metals are expensive, react slowly in acidic environments, and have high overpotentials, which limits the industrial development of water electrolysis technology.
A method for preparing a cobalt tetroxide electrolytic water catalyst using metal atoms was adopted. This method involves thermally decomposing a metal salt and a cobalt nitrate solution on a carbon cloth surface, introducing a different element such as Fe, adjusting the electronic structure of the catalyst, optimizing the adsorption free energy of the reaction intermediate, and reducing the adsorption energy barrier of OH-.
It significantly improves the catalytic activity of the catalyst, reduces the preparation cost, simplifies the process, saves energy, and the catalyst exhibits excellent oxygen evolution reaction performance in both acidic and alkaline environments.
Smart Images

Figure CN119194498B_ABST
Abstract
Description
Technical Field
[0001] This invention relates to a method for preparing a water electrolysis catalyst. Background Technology
[0002] Energy is the cornerstone of social progress, and social development is accompanied by the replacement of different energy forms. Carbon-based fossil fuels such as coal, oil, and natural gas are the main energy sources in today's society. The combustion of these fossil fuels also releases a large amount of carbon dioxide, exacerbating the greenhouse effect.
[0003] my country is vigorously promoting energy structure adjustment and developing clean energy sources such as wind, solar, hydro, and geothermal energy. However, these clean energy sources suffer from low energy density and discontinuous power supply, posing challenges to energy collection and utilization. Therefore, how to effectively utilize renewable energy has become a major issue in the energy sector today. Hydrogen energy, with its advantages of being pollution-free and having high energy density, is considered an ideal green energy source with enormous potential to become a commercially viable clean energy source. Building an energy industry chain with hydrogen as the energy conversion carrier is key to developing green energy and promoting energy conversion. Among numerous energy conversion methods, the electrolysis of water to produce hydrogen has attracted widespread attention. This method produces high-purity hydrogen with no pollutant emissions during the preparation process. In particular, proton exchange membrane electrolysis of water for hydrogen production features high current density, small equipment size, no corrosive liquids, and fast response speed. The fast response speed of water electrolysis for hydrogen production makes it easy to combine with renewable energy, has greater scalability potential, and is cleaner and more sustainable, making it the most promising green hydrogen supply method. Therefore, water electrolysis hydrogen production technology coupled with renewable energy is considered an ideal way to obtain clean energy.
[0004] Water electrolysis consists of two half-reactions: a cathodic reaction dominated by the cathode electrode and an anodic reaction dominated by the anode electrode. The cathode and anode electrode materials act as catalysts for the reactions on either side. Due to limitations in electrode reaction kinetics, a high overpotential must be overcome during water electrolysis. In actual production, excessively high overpotentials consume a large amount of electrical energy, increasing the cost of hydrogen energy and limiting the industrialization of water electrolysis technology.
[0005] To further reduce energy loss, highly active catalysts are needed to lower the overpotential of the reaction, thereby promoting its progress. Platinum (Pt), ruthenium (Ru), iridium (Ir), and their compounds are considered to be theoretically highly active water electrolysis catalysts and have already been applied in some electrocatalytic scenarios. The oxygen evolution reaction (OER) mainly occurs at the anode, and due to its complex four-electron transfer process and highly oxidizing environment, the requirements for the catalyst are more stringent. The OER reaction (2H₂O → O₂ + 4H₂O) occurs at the anode. + +4e -Iridium dioxide (IrO2) is widely recognized as the determining factor for water electrolysis efficiency because the oxygen evolution reaction (OER) is kinetically slower than the cathode HER. IrO2 is often used as a catalyst for the oxygen evolution reaction, but due to the slow kinetics of the OER in water electrolysis and the acidic environment, OH-... - The lack of precious metal catalysts results in high overpotentials, slow reactions, and high preparation costs, which limits the development of acidic water electrolysis oxygen evolution catalysts. Summary of the Invention
[0006] This invention aims to address the problems of high cost, slow reaction in acidic environments, and high overpotential of existing water electrolysis oxygen evolution catalysts prepared using precious metals and their compounds, and to provide a method for preparing a metal atom-doped cobalt tetroxide water electrolysis catalyst.
[0007] A method for preparing a metal atom-doped cobalt tetroxide electrolysis catalyst for water splitting, comprising the following steps:
[0008] 1. Dissolve cobalt nitrate in a solvent and stir until homogeneous to obtain solution A;
[0009] 2. Add the metal salt to the solvent and stir until homogeneous to obtain solution B;
[0010] 3. Solution A and solution B are sequentially added dropwise to the surface of carbon cloth, and then placed in a muffle furnace and kept at a temperature of 100℃~300℃. After keeping at this temperature, the mixture is cooled in air, thus completing the preparation method of the metal atom doped cobalt tetroxide electrolytic water catalyst.
[0011] The beneficial effects of this invention are:
[0012] This invention uses common metal salt solutions and cobalt nitrate solutions as raw materials for the reaction. The catalyst is prepared by thermal decomposition in air. The introduction of dissimilar elements significantly optimizes the adsorption free energy of the reaction intermediates, rationally adjusts the adsorption of each intermediate by the catalyst, and improves the catalytic activity of the catalyst.
[0013] 1. When the metal element in the metal salt is Fe, this invention incorporates Fe into the cobalt tetroxide catalyst, thereby adjusting the electronic structure of the catalyst by introducing Fe. The introduction of Fe causes electrons to transfer from Co to Fe, reducing the influence on OH groups. - The adsorption of these substances facilitates subsequent steps and enhances the catalytic activity of the material. This solves the problem of slow oxygen evolution reaction kinetics and high overpotential under acidic conditions.
[0014] 2. The raw materials for this invention are widely available, including chlorides, acetates, acetates, sulfates, and nitrates, making it more feasible. Compared to traditional precious metal catalysts, the selected raw materials are more inexpensive, further reducing the catalyst preparation cost.
[0015] 3. This invention introduces heterogeneous elements into the catalyst surface through a simple method, thereby regulating the adsorption of reaction intermediates and providing new active sites. The catalyst prepared by this invention has a self-supporting substrate and can be used as an electrode without additional coating. Furthermore, this catalyst exhibits excellent catalytic performance and shows great promise.
[0016] 4. The present invention has a simple process, is easy to operate, and is environmentally friendly, with a short synthesis cycle, which is beneficial for the rapid and large-scale preparation of catalysts. At the same time, the reaction requires a low temperature, which saves a lot of energy.
[0017] Instruction manual illustrations
[0018] Figure 1 This is a SEM image of the microstructure of the metal atom-doped cobalt tetroxide electrolytic water catalyst prepared in Example 1.
[0019] Figure 2 The LSV diagram shows the oxygen evolution process of water electrolysis in an acidic electrolyte using the metal atom-doped cobalt tetroxide electrolytic catalyst prepared in Example 1.
[0020] Figure 3 The LSV diagram shows the oxygen evolution process of water electrolysis in an alkaline electrolyte using the metal atom-doped cobalt tetroxide electrolytic catalyst prepared in Example 1.
[0021] Figure 4 This is a first-principles calculation diagram of the metal atom-doped cobalt tetroxide electrolytic water catalyst prepared in Example 1;
[0022] Figure 5 The XRD patterns of the metal atom-doped cobalt tetroxide electrolytic water catalyst and the undoped cobalt tetroxide electrolytic water catalyst prepared in Example 1 are as follows:
[0023] Figure 6 Raman plots of the metal atom-doped cobalt tetroxide water electrolysis catalyst and the undoped cobalt tetroxide water electrolysis catalyst prepared in Example 1:
[0024] Figure 7 High-resolution XPS images of the metal atom-doped cobalt tetroxide electrolytic water catalyst and the undoped cobalt tetroxide electrolytic water catalyst prepared in Example 1;
[0025] Figure 8 The stability test diagram of the metal atom-doped cobalt tetroxide electrolytic water catalyst prepared in Example 1 is shown.
[0026] Figure 9 LSV diagrams of the metal atom-doped cobalt tetroxide electrolytic water catalysts prepared in Example 1 and Comparative Experiment 1;
[0027] Figure 10 The LSV diagrams are for the metal atom-doped cobalt tetroxide electrolytic water catalysts prepared in Example 1 and Comparative Experiment 2. Detailed Implementation
[0028] Specific Implementation Method 1: This implementation method describes a method for preparing a metal atom-doped cobalt tetroxide electrolysis catalyst for water splitting, which is carried out according to the following steps:
[0029] 1. Dissolve cobalt nitrate in a solvent and stir until homogeneous to obtain solution A;
[0030] 2. Add the metal salt to the solvent and stir until homogeneous to obtain solution B;
[0031] 3. Solution A and solution B are sequentially added dropwise to the surface of carbon cloth, and then placed in a muffle furnace and kept at a temperature of 100℃~300℃. After keeping at this temperature, the mixture is cooled in air, thus completing the preparation method of the metal atom doped cobalt tetroxide electrolytic water catalyst.
[0032] The beneficial effects of this embodiment are:
[0033] This embodiment uses common metal salt solutions and cobalt nitrate solutions as raw materials for the reaction. The catalyst is prepared by thermal decomposition in air. The introduction of dissimilar elements significantly optimizes the adsorption free energy of the reaction intermediates, rationally adjusts the adsorption of each intermediate by the catalyst, and improves the catalytic activity of the catalyst.
[0034] 1. When the metal element in the metal salt is Fe, this embodiment incorporates Fe into the cobalt tetroxide catalyst, thereby adjusting the electronic structure of the catalyst by introducing Fe. The introduction of Fe causes electrons to transfer from Co to Fe, reducing the influence on OH-. - The adsorption of these substances facilitates subsequent steps and enhances the catalytic activity of the material. This solves the problem of slow oxygen evolution reaction kinetics and high overpotential under acidic conditions.
[0035] 2. The raw materials for this embodiment are widely available, including chlorides, acetates, acetates, sulfates, and nitrates, making it more feasible. Compared to traditional precious metal catalysts, the selected raw materials are more inexpensive, further reducing the catalyst preparation cost.
[0036] 3. This embodiment introduces heterogeneous elements into the catalyst surface through a simple method, thereby regulating the adsorption of reaction intermediates by the catalyst and providing new active sites. The catalyst prepared in this embodiment has a self-supporting substrate and can be used as an electrode without additional coating. Furthermore, this catalyst exhibits excellent catalytic performance and shows great promise.
[0037] 4. This method has a simple preparation process, is easy to operate, and involves a green reaction process with a short synthesis cycle, which is conducive to the rapid and large-scale preparation of catalysts. At the same time, the reaction requires a low temperature, which saves a lot of energy.
[0038] Specific Implementation Method Two: This implementation method differs from Specific Implementation Method One in that the concentration of cobalt nitrate in solution A in step one is 0.1 g / mL to 1 g / mL; and the concentration of the metal salt in solution B in step two is 0.01 g / mL to 0.03 g / mL. Everything else is the same as in Specific Implementation Method One.
[0039] Specific Implementation Method Three: This implementation method differs from Specific Implementation Method One or Two in that the solvent used in steps one and two is anhydrous ethanol or deionized water. Everything else is the same as in Specific Implementation Method One or Two.
[0040] Specific Implementation Method Four: This implementation method differs from Specific Implementation Methods One to Three in that the metal salt mentioned in step two is a chloride salt, acetate salt, acetic acid salt, sulfate salt, or nitrate salt. Everything else is the same as in Specific Implementation Methods One to Three.
[0041] Specific Implementation Method Five: This implementation method differs from Specific Implementation Methods One to Four in that the metal element in the metal salt described in step two is one or a combination of Fe, Ni, Ce, and Zn. Everything else is the same as in Specific Implementation Methods One to Four.
[0042] Specific Implementation Method Six: This implementation method differs from Specific Implementation Methods One to Five in that the amount of solution A added in step three is 0.1 mL / cm³. 2 ~0.2mL / cm 2 Everything else is the same as in specific implementation methods one through five.
[0043] Specific Implementation Method Seven: This implementation method differs from Specific Implementation Methods One through Six in that the amount of solution B added in step three is 0.05 mL / cm³. 2 ~0.15mL / cm 2 The rest is the same as in specific implementation methods one through six.
[0044] Specific Implementation Method Eight: This implementation method differs from Specific Implementation Methods One to Seven in that: in step three, the temperature is raised to 100℃ to 300℃ at a heating rate of 4℃ / min to 8℃ / min, and then held at 100℃ to 300℃. Everything else is the same as in Specific Implementation Methods One to Seven.
[0045] Specific Implementation Method Nine: This implementation method differs from Specific Implementation Methods One to Eight in that: in step three, the temperature is maintained at 100℃ to 300℃ for 0.5h to 3h. Everything else is the same as in Specific Implementation Methods One to Eight.
[0046] Specific Implementation Method Ten: This implementation method differs from Specific Implementation Methods One to Nine in that: in step three, the temperature is raised to 200℃ to 300℃ at a heating rate of 6℃ / min to 8℃ / min, and then maintained at 200℃ to 300℃ for 1 hour to 3 hours. Everything else is the same as in Specific Implementation Methods One to Nine.
[0047] The beneficial effects of the present invention are verified using the following embodiments:
[0048] Example 1:
[0049] A method for preparing a metal atom-doped cobalt tetroxide electrolysis catalyst for water splitting, comprising the following steps:
[0050] 1. Dissolve cobalt nitrate in anhydrous ethanol and stir until homogeneous to obtain solution A;
[0051] The concentration of cobalt nitrate in solution A is 0.5 g / mL;
[0052] 2. Add the metal salt to anhydrous ethanol and stir until homogeneous to obtain solution B;
[0053] The metal salt is ferric chloride; the concentration of the metal salt in solution B is 0.025 g / mL.
[0054] 3. Solution A and solution B were sequentially added dropwise to the surface of a carbon cloth with a size of 2cm×5cm, and then placed in a muffle furnace. The temperature was raised to 200℃ at a heating rate of 6℃ / min. The temperature was then kept at 200℃ for 1 hour. After the temperature was kept at 200℃, the mixture was cooled in air to obtain a metal atom-doped cobalt tetroxide electrolysis catalyst, named Fe-Co3O4.
[0055] The amount of solution A added was 0.125 mL / cm³. 2 ;
[0056] The amount of solution B added was 0.1 mL / cm³. 2 .
[0057] The carbon cloth mentioned in step three was purchased from Carbon Energy Technology Co., Ltd. in Taiwan, China, model number W0S1011.
[0058] Figure 1 The image shows the microstructure of the metal atom-doped cobalt tetroxide electrolytic water catalyst prepared in Example 1. As can be seen from the image, the catalyst prepared in Example 1 is composed of fine nanoparticles attached to carbon fibers.
[0059] The oxygen evolution reaction (OER) of water electrolysis was carried out using a three-electrode testing system, wherein the metal atom-doped cobalt tetroxide electrolysis catalyst prepared in Example 1 was used as the working electrode, a carbon rod pair was used as the counter electrode, a saturated calomel electrode was used as the reference electrode, and 0.5M H2SO4 solution was used as the electrolyte. Figure 2 The image shows the LSV (Laser-to-Volume Spectrum) of the metal-doped cobalt tetroxide electrolytic water catalyst prepared in Example 1 during the oxygen evolution process of water electrolysis in an acidic electrolyte. As can be seen from the image, the current density is 10 mA / cm². 2 The required overpotential is 259mV, and it exhibits excellent catalytic activity.
[0060] The oxygen evolution reaction (OER) of water electrolysis was carried out using a three-electrode testing system, wherein the metal atom-doped cobalt tetroxide water electrolysis catalyst prepared in Example 1 was used as the working electrode, a carbon rod pair was used as the counter electrode, a saturated calomel electrode was used as the reference electrode, and 1M KOH solution was used as the electrolyte. Figure 3 The image shows the LSV (Laser-to-Volume Spectrometry) of the metal-doped cobalt tetroxide electrolytic water catalyst prepared in Example 1 during the oxygen evolution process of water electrolysis in an alkaline electrolyte. As can be seen from the image, the current density is 10 mA / cm². 2 The required overpotential is 203 mV, and it exhibits excellent catalytic activity.
[0061] Figure 2 and Figure 3 This demonstrates that the metal atom-doped cobalt tetroxide electrolysis catalyst prepared in Example 1 exhibits excellent OER catalytic activity under both acidic and alkaline environments.
[0062] Figure 4 The figure shows the first-principles calculation diagram of the metal-doped cobalt tetroxide electrolytic water catalyst prepared in Example 1. As can be seen from the figure, the introduction of Fe optimizes the electron distribution on the catalyst surface. Compared with the original Co3O4 matrix, the introduction of Fe reduces the catalyst's resistance to OH-. - The adsorption of Fe is more conducive to the conversion of *OH to *O, which optimizes the adsorption of reaction intermediates by the catalyst and improves the electrocatalytic activity of the material.
[0063] Figure 5The XRD patterns of the metal-doped cobalt tetroxide electrolysis catalyst and the undoped cobalt tetroxide electrolysis catalyst prepared in Example 1 are shown in the figures. As can be seen from the figures, the introduction of Fe element lowers the diffraction peaks of the catalyst XRD, indicating a decrease in the crystallinity of the material. The introduction of metal atoms successfully controlled the crystallinity of the catalyst. The low crystallinity material, due to its numerous grain boundaries and more diffusion channels, increases its contact area with the electrolyte, thereby improving the catalytic performance of the catalyst.
[0064] Figure 6 Raman spectroscopy plots of the metal atom-doped cobalt tetroxide electrolysis catalyst and the undoped cobalt tetroxide electrolysis catalyst prepared in Example 1: As can be seen from the figure, the introduction of Fe element broadens the Raman diffraction peak position of the catalyst, which means that the introduction of Fe element reduces the crystallinity of the material, provides more channels for liquid exchange and diffusion, exposes more of the catalyst activity, and improves the catalytic performance of the catalyst.
[0065] Figure 7 High-resolution XPS images of the metal-doped cobalt tetroxide electrolytic water catalyst and the undoped cobalt tetroxide electrolytic water catalyst prepared in Example 1 are shown. Fe can effectively adjust the electronic structure of the catalyst, with electrons transferring from Co to Fe. The enrichment of electrons around Fe weakens the effect on OH groups. - Adsorption, in Figure 4 This has been proven in practice.
[0066] The oxygen evolution reaction (OER) of water electrolysis was carried out using a three-electrode testing system, wherein the metal atom-doped cobalt tetroxide electrolysis catalyst prepared in Example 1 was used as the working electrode, a carbon rod pair was used as the counter electrode, a saturated calomel electrode was used as the reference electrode, and 0.5M H2SO4 solution was used as the electrolyte. Figure 8 This is a stability test diagram of the metal atom-doped cobalt tetroxide electrolytic water catalyst prepared in Example 1. The stability was determined at a current density of 10 mA / cm². 2 The catalyst can operate stably for 35,000 seconds, demonstrating excellent stability.
[0067] Comparative Experiment 1: This comparative experiment differs from Example 1 in that: in step 2, ferric chloride is replaced with strontium chloride, and strontium chloride is dissolved in deionized water and stirred evenly to obtain solution B; the concentration of strontium chloride in solution B is 0.0125 g / mL; in step 3, the dropwise addition volume of solution B is 0.05 mL / cm³. 2 The metal-doped cobalt tetroxide electrolysis catalyst prepared in step three was named Sr-Co3O4. Everything else was the same as in Example 1.
[0068] The oxygen evolution reaction (OER) of water electrolysis was carried out using a three-electrode testing system, wherein the metal atom-doped cobalt tetroxide electrolysis catalyst prepared in Example 1 or Comparative Experiment 1 was used as the working electrode, a carbon rod pair was used as the counter electrode, a saturated calomel electrode was used as the reference electrode, and 0.5M H2SO4 solution was used as the electrolyte. Figure 9 The LSV diagrams show the metal atom-doped cobalt tetroxide electrolytic water catalysts prepared in Example 1 and Comparative Experiment 1. As can be seen from the diagrams, the current density is 10 mA / cm². 2 The catalyst prepared in Example 1 required an overpotential of 259 mV, while the catalyst prepared in Experiment 1 required an overpotential of 370 mV, demonstrating that the different doping elements can greatly affect the catalytic activity of the material.
[0069] Comparative Experiment 2: This comparative experiment differs from Example 1 in that the amount of solution B added in step 3 is 0.025 mL / cm³. 2 The metal-doped cobalt tetroxide electrolysis catalyst prepared in step three was named Fe-Co3O4-1. Everything else was the same as in Example 1.
[0070] The oxygen evolution reaction (OER) of water electrolysis was carried out using a three-electrode testing system, wherein the metal atom-doped cobalt tetroxide electrolysis catalyst prepared in Example 1 or Comparative Experiment 2 was used as the working electrode, a carbon rod pair was used as the counter electrode, a saturated calomel electrode was used as the reference electrode, and 0.5M H2SO4 solution was used as the electrolyte. Figure 10 The LSV diagrams show the metal atom-doped cobalt tetroxide electrolytic water catalysts prepared in Example 1 and Comparative Experiment 2. As can be seen from the diagrams, the current density is 10 mA / cm². 2 The catalyst prepared in Example 1 required an overpotential of 259 mV, while the catalyst prepared in Comparative Experiment 2 required an overpotential of 290 mV, demonstrating that the amount added can greatly affect the catalytic activity of the material.
Claims
1. A method for preparing a metal atom-doped cobalt tetroxide electrolytic water catalyst, characterized in that... It is done in the following steps:
1. Dissolve cobalt nitrate in anhydrous ethanol and stir until homogeneous to obtain solution A; The concentration of cobalt nitrate in solution A is 0.5 g / mL; 2. Add the metal salt to anhydrous ethanol and stir until homogeneous to obtain solution B; The metal salt is ferric chloride; the concentration of the metal salt in solution B is 0.025 g / mL.
3. Solution A and solution B were sequentially added dropwise to the surface of a carbon cloth with a size of 2cm×5cm, and then placed in a muffle furnace. The temperature was raised to 200℃ at a heating rate of 6℃ / min. The temperature was then kept at 200℃ for 1 hour. After the temperature was kept at 200℃, the mixture was cooled in air to obtain a metal atom-doped cobalt tetroxide electrolytic water catalyst. The amount of solution A added was 0.125 mL / cm³. 2 ; The amount of solution B added was 0.1 mL / cm³. 2 ; The prepared metal-atom-doped cobalt tetroxide electrolysis catalyst was used for oxygen evolution in water electrolysis under acidic or alkaline conditions; using 0.5M H2SO4 solution as the electrolyte, at a current density of 10 mA / cm²... 2 Below, the overpotential is 259mV; Using 1M KOH solution as the electrolyte, at a current density of 10 mA / cm² 2 The overpotential is 203mV.
Citation Information
Patent Citations
Ir-doped Co3O4 nano-catalyst, preparation method and application thereof, and metal-air battery
CN117673383A
Bifunctional electrode and preparation method thereof and its application for zinc-air battery
TWI827263B
